Konsep Inseminasi Buatan pada Manusia dalam Perspektif Maqashid Syariah (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research aims to determine the review of Islamic law regarding artificial insemination in humans. And to find out the maqashid of sharia on artificial insemination in humans. This research was carried out using library research and paying attention to the field (Field Research). Literature study is a process of searching for various literature, study results related to the research to be conducted. Literature study can be likened to a key that will open everything that can help solve research problems. The results of the research show that artificial insemination in humans in terms of Islamic law is (1) sperm cells and ovum from the husband and wife themselves, and the embryos are not transferred into the womb of another woman (entrusted mother), if the condition of the husband and wife concerned really requires it and (2) artificial insemination or IVF with sperm and/or ovum donors brings more harm than good. The problem is that it can help married couples where both or one of them is infertile or there are natural obstacles in the husband and/or wife that prevent sperm cells from meeting with egg cells. Yusuf Qaradawi said that if sperm comes from another man, whether known or unknown, then this is forbidden. Likewise, if the egg cells come from another woman, or the egg cells belong to the wife, but the uterus belongs to another woman, this is not allowed. Sheikh Mamud Syaltut said that artificial insemination uses the sperm of another man (not her husband). The law is the same as adultery and children born as a result of this kind of insemination have the same status as children born outside of a valid marriage. The Maqashid of Sharia on artificial insemination in humans is hifdzun nasab (protecting the succession of descendants) because children are included in the requirements of doruriyat in marriage. although human insemination (IVF) does carry some risks of death and post-natal disorders. Artificial insemination in humans with sperm and ovum donors will bring more harm (negative impacts) than benefits (positive impacts). Among the benefits is helping husband and wife who are infertile, either both or one of them, to have offspring or who experience problems with normal fertilization.